The Role of Public Accountability in Mediating The Effect of Social Capital on Village-Owned Enterprises Performance - Suryanto, Rudy; Utami, Tiyas Puji; Darmawan, Rahmat; Fitriani, Khoirunnisa; Widiastuti, Harjanti (Universitas Muhammadiyah Malang, 2026)
Research Objective: This study aims to examine the effect of social capital on improving the performance of village-owned enterprises (VOEs) by considering public accountability as a mediator. Method/approach: This research is a survey research using questionnaires distributed directly to respondents. The data obtained consisted of 250 VOEs from Central Java Province, Indonesia. Sampling using purposive sampling technique. Data analysis was carried out using structural equation models. Results: The results showed that social capital has a positive effect on improving the performance of VOEs, and the results of public accountability partially mediate the effect of social capital on VOEs performance. Practice implications: Practically, the findings imply that strengthening social capital and public accountability need to be institutional strategies in the development of VOEs to improve performance and legitimize long-term sustainability. Originality/novelty: The novelty of this research lies in the placement of public accountability as a mediating variable that bridges the influence of social capital on VOEs performance within the Institutional Theory framework through the simultaneous integration of its three pillars: normative, cognitive-cultural, and regulative